Estrogen receptor α regulates phenotypic switching and proliferation of vascular smooth muscle cells through the NRF1-OMI-mitophagy signaling pathway under simulated microgravity - Jiang, Min; Liu, Zifan; Shao, Junjie; Zhou, Jingjing; Wang, Haiming; Song, Chao; Li, Xin; Wang, Lin; Xu, Qiang; Liu, Xiaojuan; Lin, Lejian; Zhang, Ran (Frontiers in Physiology, 2022)
Vascular remodeling during microgravity exposure results in postflight cardiovascular deconditioning and orthostatic intolerance in astronauts. To clarify the underlying mechanism, we investigated whether estrogen receptor α (ERα)-NRF1-OMI-mitophagy signaling was involved in the dedifferentiation and proliferation of vascular smooth muscle cells (VSMCs) under simulated microgravity. Phenotypic markers, mtDNA copy number and mitochondrial biogenesis, mitochondrial dynamics and mitophagy in rat thoracic artery smooth muscle cells were examined. Four-week hindlimb unweighting (HU) was used to simulate microgravity in rats and 10% serum was used to induce VSMCs dedifferentiation in vitro. The effects of ERα-NRF1-OMI signaling on mitophagy, phenotypic switching and proliferation of VSMCs, and cerebrovascular remodeling in HU rats were studied by genetic manipulation and chronic drug intervention. We found that ERα is positively associated with contractile phenotype switching but inversely correlated with synthetic phenotype switching and proliferation of VSMCs both in vivo and in vitro. During the dedifferentiation process of VSMCs, reduced mtDNA copy number, disturbed mitochondrial biogenesis and respiration, and perturbed fission-fusion-mitophagy signaling were detected, which were reversed by ERα overexpression. Mechanistically, the ERα downstream protein OMI preserved the mitochondrial Parkin level by increasing its protein stability, thereby protecting mitophagy. In line with this, we found that activating ERα signaling by PPT could alleviate the synthetic phenotype switching and proliferation of HU rat cerebral VSMCs by reestablishing fission-fusion-mitophagy hemostasis. The current study clarified a novel mechanism by which inhibited ERα-NRF1-OMI-mitophagy signaling resulted in synthetic phenotype switching and proliferation of VSMCs and cerebrovascular remodeling under simulated microgravity.